2D Material‐Based Heterostructures for Rechargeable Batteries. Issue 4 (26th June 2021) - Wang, Shijian; Zhao, Sai; Guo, Xin; Wang, Guoxiu
Abstract: 2D materials are regarded as promising electrode materials for rechargeable batteries because of their advantages in providing ample active sites and improving electrochemical reaction kinetics. However, it remains a great challenge for 2D materials to fulfill all requirements for high‐performance energy storage devices in terms of electronic conductivity, the number of accessible active sites, structural stability, and mass production capability. Recent advances in constructing 2D material‐based heterostructures offer opportunities for utilizing synergistic effects between the individual blocks to achieve optimized properties and enhanced performance. In this perspective, the latest advances of 2D material‐based heterostructures are summarized, with particular emphasis on their multifunctional roles in high‐performance rechargeable batteries. Synthetic strategies, structural features in mixed dimensionalities, structure engineering strategies, and distinct functionalities of the 2D material‐based heterostructures in various electrochemical applications are systematically introduced. Finally, challenges and perspectives are presented to highlight future opportunities for developing 2D material‐based heterostructures for practical energy storage. Abstract : 2D material‐based heterostructures are widely employed in rechargeable batteries. This perspective summarizes the latest advances of 2D material‐based heterostructures, including synthetic strategies, structural features in mixed dimensionalities (0D to 2D), structure engineering strategies (surface chemistry and defect engineering), and their distinct functionalities (boosted charge transfer and ion diffusion, restricted volume expansion, and increased electrochemical reactivity) in rechargeable batteries.